VISTA and PD-L1 synergistically predict poor prognosis in patients with extranodal natural killer/T-cell lymphoma - He, Hai-Xia (Oncoimmunology, 2021)
Although PD-1/PD-L1 blockade therapy confers salutary effects across cancer types, their efficacy in Extranodal Natural killer/T-cell lymphoma (ENKTCL) patients is limited and unpredictable. Here, we comprehensively evaluated the expression profile of a panel of immune-regulatory makers to identify novel prognostic biomarkers and/or therapeutic targets for this malignancy. Using immunohistochemistry and multiplex immunofluorescence, we found that the expression of VISTA (88.1%) was predominantly in CD68+ macrophages and much higher than PD-L1 expression (68.7%) in ENKTCL. B7-H4 and HHLA2 proteins were not detected in ENKTCL. B7-H3 was expressed in minority of ENKTCL patients (13.7%) and mainly colocalized with CD31. A close correlation was detected between VISTA and PD-L1, but they were not co-expressed in the same cells. High expressions of VISTA or PD-L1 were significantly associated with detrimental clinicopathological characteristics, dismal prognosis, and high density of CD8+ TILs, and high VISTA expression was also significantly associated with high density of Foxp3+ TILs. VISTA combined with PD-L1 was an independent prognostic factor for PFS and OS. Moreover, the patients with high VISTA showed a poor response to PD-1 blockades in ENKTCL. In conclusion, these findings provide a rationale for VISTA as an ideal immunotherapeutic target next to PD-L1 for ENKTCL.